2015
DOI: 10.1038/srep15233
|View full text |Cite
|
Sign up to set email alerts
|

High Elastic Moduli of a 54Al2O3-46Ta2O5 Glass Fabricated via Containerless Processing

Abstract: Glasses with high elastic moduli have been in demand for many years because the thickness of such glasses can be reduced while maintaining its strength. Moreover, thinner and lighter glasses are desired for the fabrication of windows in buildings and cars, cover glasses for smart-phones and substrates in Thin-Film Transistor (TFT) displays. In this work, we report a 54Al2O3-46Ta2O5 glass fabricated by aerodynamic levitation which possesses one of the highest elastic moduli and hardness for oxide glasses also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
51
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 39 publications
(49 reference statements)
1
51
2
Order By: Relevance
“…As a result, the glass with the highest Al 2 O 3 content ( x  = 60) with mullite composition shows the highest elastic moduli and Vickers hardness. These values are comparable to hard glasses, such as R 2 O 3 –SiO 2 –Al 2 O 3 or CaO–SiO 2 –Al 2 O 3 glasses, and are much larger than those of crack-resistant silicate or borosilicate glasses789101112131819202122232425.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…As a result, the glass with the highest Al 2 O 3 content ( x  = 60) with mullite composition shows the highest elastic moduli and Vickers hardness. These values are comparable to hard glasses, such as R 2 O 3 –SiO 2 –Al 2 O 3 or CaO–SiO 2 –Al 2 O 3 glasses, and are much larger than those of crack-resistant silicate or borosilicate glasses789101112131819202122232425.…”
Section: Resultsmentioning
confidence: 79%
“…In case of alkali–alkaline earth silicate glasses, it was found that glasses with more packed structures had higher values of hardness and the elastic modulus6. Al 2 O 3 – R 2 O 3 and Al 2 O 3 –SiO 2 – R 2 O 3 glasses ( R : Y, Sc, or Ta) are among the hardest oxide glasses ( H V up to 9.5 GPa) with high elastic moduli ( E up to 169 GPa)78910111213. This is attributed to their high atomic packing density and high dissociation energy unit volume of components.…”
mentioning
confidence: 99%
“…This enables the suppression of heterogeneous nucleation from the container wall and promotes deep undercooling and vitrification of the melt. In recent years, Al 2 O 3 -1112131415, TiO 2 -1617181920, Nb 2 O 5 -212223, and WO 3 -based24 glasses without any network formers have been discovered using this method. These “unconventional” glasses showed outstanding dielectric, optical, and mechanical properties as a result of the specific glass compositions and structures.…”
mentioning
confidence: 99%
“…In such oxide glasses, three kinds of Al coordination exist: 4-coordinated [4] Al, 5-coordinated [5] Al, and 6-coordinated [6] Al, which can all be quantitatively measured by magic angle spinning nuclear magnetic resonance (MAS NMR) [3] [4]. Using structural analysis of aluminate glasses using MAS NMR, it has been clarified that their physical properties, such as fictive temperature, microhardness, elastic modulus, and refractive index, are closely related to their Al coordination [5] [6] [7] [8]. Therefore, it is important to control Al coordination in oxide glasses for adjustments of those physical properties.…”
mentioning
confidence: 99%